INFLUENCE OF GOAT DUNG ON SOIL PROPERTIES, GROWTH AND YIELD OF MAIZE IN GWAGWALADA, FCT, NIGERIA - Abdulkareem, Yusuf Jiddah; Tella, Yusuf O.; Shuaib , Muhammad Bashir; Saka, Idowu Eletu; Muhammad , Aminu N.; Baba Nitsa, Mohammed; Nduka, Beatrice A. (FUDMA JOURNAL OF SCIENCES, 2024)
Farmers in the Guinea Savannah region of Nigeria rely on inorganic fertilizer to mitigate yield reduction caused by low soil fertility. Unfortunately, high purchasing cost and harmful residual effect of chemical fertilizers render them unsustainable. However, goat dung, which is an animal waste, can be harnessed as organic amendment. Therefore, a field experiment was conducted at the Teaching and Research Farm, Faculty of Agriculture, University of Abuja, Nigeria to evaluate growth and yield response of maize to goat dung amended soils. Three levels of goat dung (0 kg, 1.8 kg, and 2.7 kg of goat dung) were incorporated into the soil during land preparation. A Randomized Complete Block Design (RCBD) was used for arranging the treatments, which were replicated three times. Vegetative components: plant height, leaf area, number of leaves, as well as yield parameters: cob length, cob diameter, cob weight, number of seeds/cob, 1000 seed weight and seed yield were evaluated and subjected to Analysis of Variance (ANOVA) using GenStat statistical software (17th Edition). Significantly different means were separated using Duncan New Multiple Range Test (DNMRT) at 5% level of significance. Result showed that application of goat dung increased soil properties (pH, organic matter content, total N, available P, CEC, exchangeable K, Na, Ca, Mg) and improved growth and yield of maize; however, increments were not significant. Thus, further trials are recommended using higher quantities of goat dung.
Keywords: Goat dung, Growth, Maize, Soil amendment, Yield; Goat dung; Growth; Maize; Soil amendment; Yield